Essential statistical concepts for the quality professional - Stamatis, D. H. (Boca Raton, FL Taylor & Francis, 2012)
Many books and articles have been written on how to identify the "root cause" of a problem. However, the essence of any root cause analysis in our modern quality thinking is to go beyond the actual problem. This book offers a new non-technical statistical approach to quality for effective improvement and productivity by focusing on very specific and fundamental methodologies as well as tools for the future. It examines the fundamentals of statistical understanding, and by doing that the book shows why statistical use is important in the decision making process.
Includes bibliographical references and index.
Keywords: Quality control -- Statistical methods